Menstrual hygiene practices and WASH practices among women residing in an urban slum in Delhi: a community-based study - Sahdev Santra; Nitin Panwar; Sahil Dhama; Abin K. Rajan; Parth Singhal; Anita Verma (International Journal Of Community Medicine And Public Health, 2026)
Background: Menstrual hygiene management (MHM) is a vital component of women’s health, yet it remains a neglected issue in low-resource settings. Despite improved product availability, women in urban slums continue to face challenges related to sanitation, privacy, and hygiene. This study aimed to assess menstrual hygiene practices among women in an urban slum of Delhi and examine their association with WASH (water, sanitation, and hygiene) behaviours. Methods: A community-based cross-sectional study was conducted among 307 women of reproductive age residing in an urban slum of Delhi. Data were collected using a pretested, semi-structured questionnaire based on the menstrual practice questionnaire (MPQ) and WASH indicators. Descriptive and inferential statistics were applied to analyse menstrual hygiene practices and their association with hygiene-related outcomes. Results: Of the 307 participants, 60% were below 30 years and 81.4% were literate. Use of disposable sanitary pads was nearly universal- 93.5% at home and 95.1% outside- while 2.6% used cloth. Only 66.1% reported washing hands before changing menstrual materials compared to 92.8% after. Most women (94.1%) used soap or detergent, and 90.6% practiced daily genital washing. Household garbage was the most common disposal method (69.7%), while 8.1% used unsafe methods. Symptoms suggestive of urinary tract infection (UTI) were significantly associated with inadequate handwashing (p